Social capital as a political strategy: evidence from Nasdem Party in Makassar City, Indonesia - Suhardiman Syamsu; Andi Muhammad Rusli; Miranda Malinda Hamka (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The social capital in a general election is understudied compared to the economic capital. This study discusses the social capital of the Nasional Demokrat (Nasdem) party in the 2019 legislative election. Nasdem was in the top three rows of political party seats in the legislative election and won the most votes in the city of Makassar. This study used primary data collected from various related stakeholders: Nasdem’s agent/organizer, Nasdem's legislative candidate, community leader, general election commissioner, and residents/voters. Content analysis based on in-depth interviews found the significant relation of social capital with Nasdem's strategy in winning the 2019 legislative election in Makassar. Therefore, social capital could be a theoretical and practical discussion in a general election, especially for the political party. More specifically, social capital in Nasdem strategy refers to bonding and bridging social capital, which was in the form of disaster care programs, free ambulance, family and friendship relations, and sons of the regions discourse. The study contributes to evidence of social capital implementation to political party strategy for winning the general election.